Polypyrrole synthezited with oxidative cerium(IV) ions - Saraç, A. S.; Erbil, C.; Ustamehmetoğlu, B. (Springer Science and Business Media LLC, 1994)
The chemical oxidation of pyrrole by Ce(IV) salts in aqueous solutions or water-acetonitrile system has been studied. Products were characterized by elementel analyses, FT-IR and conductivity measurements. Conductivity values of polypyrrole complexes synthesized in aqueous solutions are comparable with those in acetonitrile-water, if suitable oxidant/monomer ratio and [H+] are selected.